VISUAL STORYTELLING ANALYSIS IN THE FILM “GRUSAH GRUSUH” ABOUT MISSCOMMUNICATION - Octavianto, Rozzy Aditya; Aeshtetika, Nur Maghfirah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine how visual storytelling techniques in Paniradya Kaistimewan's short film Grusah Grusuh depict the theme of communication breakdown among citizens. Method: A descriptive qualitative approach was employed, analyzing 15 selected scenes using Bruce Block’s framework of seven visual components—space, line, shape, tone, color, movement, and rhythm. Data were gathered through observation and documentation, with scene selection based on their thematic relevance to miscommunication and social tension. Results: The analysis reveals that visual elements such as the use of deep space, line closure, contrasting and saturated colors, dynamic tracking shots, and rhythmic repetition of audio-visual patterns effectively create narrative tension and convey the consequences of poor communication without relying heavily on dialogue. Novelty: This study contributes to the discourse on film and communication studies by highlighting the role of visual storytelling as a powerful medium for representing social issues. It demonstrates that the integration of cinematic techniques can substitute for verbal expression in illustrating the dynamics of miscommunication and its impact on communal relationships, an area rarely explored in prior research on short films.